Self-Guided Intense Laser Pulse Propagation in Air - Danielius, R.; Mikalauskas, D.; Dubietis, A.; Piskarskas, A. (Nonlinear Analysis: Modelling and Control, 2001)
We report on observation of self-guiding of picosecond laser pulses in air that produces large-scale self-phase modulation. The converging picosecond laser beam produced a confined filament over 3 m of propagation with the whitelight spectrum.